The Effectiveness Of The Death Criminal Threat In The Framework Of Narcotics Crime Handling - Didik Risdiyanto (Jurnal Hukum Khaira Ummah, 2021)
The problems studied and analyzed include how the effectiveness of the death penalty in dealing with narcotics crimes and the death penalty can cause a deterrent effect on narcotics abuse. In Law no. 35 of 2009 concerning Narcotics, there is a death penalty. The eradication of narcotics is not only a discourse, but law enforcement officers such as the police and others must also participate in helping to eradicate narcotics in order to achieve the prosperity and welfare of the Republic of Indonesia that is free from drugs. As a sovereign country, of course, in terms of eradicating narcotics, the government must continue to increase efforts in providing counseling and understanding about the dangers of narcotics and their sanctions as a preventive effort for narcotics circulation so that they can make people aware of the dangers of narcotics. To overcome the widespread circulation of narcotics, in Law no.